Intratracheal Administration of Chloroquine-Loaded Niosomes Minimize Systemic Drug Exposure - Hesham A. Saafan; Kamilia M. Ibrahim; Yasmeena Thabet; Sara M. Elbeltagy; Rana A. Eissa; Ashraf H. Ghaleb; Fathy Ibrahim; Mahmoud Elsabahy; Noura G. Eissa (MDPI AG, 2021)
Pulmonary administration provides a useful alternative to oral and invasive routes of administration while enhancing and prolonging the accumulation of drugs into the lungs and reducing systemic drug exposure. In this study, chloroquine, as a model drug, was loaded into niosomes for potential pulmonary administration either via dry powder inhalation or intratracheally. Chloroquine-loaded niosomes have been prepared and extensively characterized. Furthermore, drug-loaded niosomes were lyophilized and their flowing properties were evaluated by measuring the angle of repose, Carr's index, and Hausner ratio. The developed niosomes demonstrated a nanosized (100-150 nm) spherical morphology and chloroquine entrapment efficiency of ca. 24.5%. The FT-IR results indicated the incorporation of chloroquine into the niosomes, whereas in vitro release studies demonstrated an extended-release profile of the drug-loaded niosomes compared to the free drug. Lyophilized niosomes exhibited poor flowability that was not sufficiently improved after the addition of lactose or when cryoprotectants were exploited throughout the lyophilization process. In vivo, intratracheal administration of chloroquine-loaded niosomes in rats resulted in a drug concentration in the blood that was 10-fold lower than the oral administration of the free drug. Biomarkers of kidney and liver functions (i.e., creatinine, urea, AST, and ALT) following pulmonary administration of the drug-loaded nanoparticles were of similar levels to those of the control untreated animals. Hence, the use of a dry powder inhaler for administration of lyophilized niosomes is not recommended, whereas intratracheal administration might provide a promising strategy for pulmonary administration of niosomal dispersions while minimizing systemic drug exposure and adverse reactions.